Hematological abnormalities in oral lichen planus, recurrent aphthous ulceration and stomatis or glossitis - Kobkan Thongprasom; Pornpan Youngnak; Vilaiwan Aneksuk (Chulalongkorn University, 2008)
Objective. The aim of this study was to analyse the hematologic status if Thai patients with oral lichen planus (OLP), recurrent aphthous ulceration (RAU) and stomatitis or glossitis (ST/GT). Study design. Sixty one patients were examined consecutively for hematological abnormalities including serum folate, red cell folate and serum vitamin B[subscribe12] levels. The patient were divide into 3 major groups with OLP(22), RAU(19) and ST/GT(20). Result. Low red cell folate and low serum with red cell folate were found in patients with OLP (11/22) , RAU(11/99) and ST/GT(8/20). However, there was no statistically significant difference in folate deficiencies among these groups (P.0.05). Low serum vitamin B[subscribe12] levels were found in only 5 of 61 cases. Gastrointestinal disorders were found in 15 of all these groups. Treatment in patients with deficiencies showed good response in approximately 46.3% of the cases. Conclusion. Investigations for folate and vitamin B[subscribe12] levels are recommended in patients with refractory oral lesions for the benefit of treatment.